Ferramenta de conversão de modelos de sistemas de automação em rede de Petri para linguagem Ladder - Freire, Eduardo Lopes (Universidade Federal de São Carlos, 2025)
Programmable Logic Controllers (PLCs) are extensively used in the automation of industrial processes to enhance efficiency, quality, and safety in sequential workflows. With the increasing complexity of the systems to be automated, programming PLCs has progressively become more difficult to learn, implement, maintain, and build upon. In response to this growing complexity, methods have been developed for modeling these systems and implementing them in standard programming languages, which can later be adapted for any PLC. The most popular language used for PLC programming is Ladder Diagram Language, which, although simplifying the understanding of the system due to the conversion often being done intuitively and manually, can still lead to unexpected effects caused by human interpretation errors. This work aims to recover, adapt, and complement a solution for converting automated system models into Ladder language (proposed by Rodrigo, 2018), making the process automatic. The text discusses the conversion process used (proposed by Kato, 2023), the auxiliary tools required for the system's workflow, and the decisions made to recover the system's functionality, expand its features, and execute it in a straightforward manner.
Converting toll of automation system models in Petri net to PLC Ladder diagram language
Keywords: Redes de Petri; Petri Net; PLC; Controlador Lógico Programável; Programmable Logic Controller; Ladder Diagram; Diagrama Ladder; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS::AUTOMACAO ELETRONICA DE PROCESSOS ELETRICOS E INDUSTRIAIS